Analysis of Flooding Potential Using ARC-GIS in Ranai Island, Natuna Regency - Deon Libora; Ade Jaya Saputra (Journal of Civil Engineering and Planning (JCEP), 2023)
Flood is a problem that occurs frequently on Ranai Island, Natuna Regency, especially in the last three years namely 2021, 2022, and 2023, where 2022 recorded the most severe flood among them. The data used in this study includes Digital Elevation Model (DEM), Landcover data, Slope data, and Precipitation data, all of which are secondary data. This study aims to analyze the potential of flood inundation using ArcGIS on Ranai Island, Natuna Regency. The research focuses on the use of ArcGIS 10.8 application as the sole platform for analysis. The Weighted Sum analysis method is used to combine data from various sources to map areas that are potentially prone to flood inundation. The research results in a flood inundation map indicating flood-prone areas. The research findings also indicate that flood-inundated areas in previous years are indeed located in flood-prone areas. This map is expected to provide valuable information for urban planning and hydrological analysis, as well as to serve as a guide in flood disaster mitigation efforts on Ranai Island. The conclusion of this research emphasizes the importance of mapping the potential of flood inundation as an initial step in facing flood risks in the future. The flood inundation map produced is expected to be an effective tool for stakeholders in making decisions related to urban planning and natural resource management on Ranai Island, Natuna Regency.